2007
DOI: 10.1016/j.jss.2006.12.558
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Interrupts TGF-β1 Signaling Between Gallbladder Epithelial Cells and Myofibroblasts

Abstract: Background-The cellular and molecular mechanisms of fibrogenesis in the extrahepatic biliary epithelium are not known. TGF-β1 is a cytokine implicated in signaling pathways that mediate collagen formation. An observation that paclitaxel (PT), applied topically into the rat common bile duct, inhibited stricture formation led us to hypothesize that PT's effects might be due to interruption of TGF-β1 signaling between biliary epithelial cells and subepithelial myofibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
(51 reference statements)
2
25
0
Order By: Relevance
“…HIBEpiCs were cultured in RIMP1640 supplemented with 10% fetal bovine serum (FBS), at 37 C in a 5% CO 2 humidified atmosphere. Because TGF-b1 mRNA was markedly up-regulated when the concentration of LPS reached 2 mg/mL in vitro [8], cells were stimulated with LPS at a concentration of 2 mg/mL at different time points.…”
Section: Cell Culturementioning
confidence: 99%
“…HIBEpiCs were cultured in RIMP1640 supplemented with 10% fetal bovine serum (FBS), at 37 C in a 5% CO 2 humidified atmosphere. Because TGF-b1 mRNA was markedly up-regulated when the concentration of LPS reached 2 mg/mL in vitro [8], cells were stimulated with LPS at a concentration of 2 mg/mL at different time points.…”
Section: Cell Culturementioning
confidence: 99%
“…Moreover, it has been reported that paclitaxel ameliorates fibrosis in hepatic stellate cells and renal fibrosis through the inhibition of TGF-β/Smad activity (6,7). Paclitaxel also interrupts TGF-β1 signaling between gallbladder epithelial cells and myofibroblasts (19). Taghian et al reported that paclitaxel decreases interstitial fluid pressure and improves oxygenation in breast cancer tissues in patients treated with neoadjuvant chemotherapy and that patients with hypoxic tumors and/or tumors with high interstitial fluid pressure may start with paclitaxel chemotherapy to improve their physiological status (20).…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose paclitaxel (71)(72)(73)(74), metformin (75)(76)(77), angiotensin receptor blocker (ARB) (61,78), statins (79,80) and histone deacetylase inhibitors (HDACis) (81,82) have all been indicated as agents that can inhibit the EMT of tumor cells or activation of stromal cells. There are a number of studies investigating the effects of these drugs and cancer treatments: For instance, metformin has been epidemiologically demonstrated to suppress tumor metastasis (83,84), whereas Nakai et al (85) demonstrated that inhibition of the renin-angiotensin system affects the prognosis of patients with advanced pancreatic cancer receiving GEM.…”
Section: Effect Of Preoperative Therapy On Pancreatic Cancer Tissuesmentioning
confidence: 99%